(untitled) (Journal of Management and Social Sciences, 2023)
One of the main goals of the international movement for sustainable development, supported by the UN, is the quest for the political inclusion of people with disabilities in political participation generally and the electoral process specifically. In Nigeria, there seem to be no formal barriers to electoral participation of persons with disabilities. However, the electoral participation of persons with disabilities seems to be minimal. Therefore, this study aimed at investigating the barriers to electoral participation for persons with disabilities in the 2019 general elections in Oyo state, Nigeria. Oyo state is selected for this study because the Federal College of Education (Special), Oyo has the largest conglomeration of disabled students that could be found in any higher institution in Nigeria. This study opted for a mixed method by utilizing both quantitative and qualitative methods of data collection. For the quantitative method, this study utilized the descriptive survey research design. For the qualitative method, focus group discussion was utilized to collect data from the members of the Joint Actions of Persons with Disabilities (JONAPWP) Oyo chapter. 400 questionnaires were distributed to disabled persons who are purposively selected for the survey. In analyzing the data, the quantitative data were analysed using descriptive statistics. Data and evidence gathered from the field were analysed through the use of bar chart and percentage. The qualitative data were analysed using narrative analysis technique. The findings revealed that the predominant barriers to electoral participation for persons with disabilities were lack of access to polling stations, stigmatization and financial constraint, while the minor barriers were lack of support from INEC officials, information accessibility and unsupportive legislation. The study concluded that stigmatization and discrimination of persons with disabilities could further lead to low electoral participation of disabled people in election. It is therefore recommended that creating an enabling environment that promotes accessibility and eliminates discriminatory practices against PWDs will do the magic.